Pharmacological treatment for apnoea of prematurity—the need for an individualised approach - Fatunla, Odunayo A. T.; Shakir, Nishadh A.; Zandvoort, Coen S.; Cobo, Maria M.; van den Anker, John; Hartley, Caroline (Frontiers in Pediatrics, 2025)
Apnoea—the cessation of breathing—is a common condition in preterm infants due to the immaturity of their lungs, airway and brainstem respiratory drivers. Consequently, many preterm infants will receive pharmacological interventions for the treatment of apnoea. Caffeine (or in some developing countries, aminophylline or theophylline) is usually given as first-line treatment, whereas doxapram is sometimes used as an adjunct therapy. These treatments reduce apnoeas and improve neurodevelopmental outcomes. However, there is substantial variation in individual infants’ requirement for treatment (not all infants will experience apnoea nor to the same degree). Moreover, there are considerable differences in how infants respond to treatment, for example, some infants continue to experience episodes of apnoea despite treatment. Clinical guidelines for pharmacological treatment (in particular, for caffeine) are often based on the age or weight of the infant, and there are currently no biomarkers for treatment requirement or dosing. There is a need for personalised treatment for apnoea of prematurity through the identification of suitable pharmacodynamic biomarkers. Here we narratively review current knowledge of the treatment of apnoea, focusing on caffeine, aminophylline and doxapram. We propose potential pharmacodynamic biomarkers and explore avenues for future research which will enable the testing and translation of these biomarkers for use in the neonatal unit. A personalised approach for apnoea treatment is essential to mitigate the negative short and long-term effects of both apnoea and its treatment in premature infants, ensuring that treatment can be provided at the right time and with the correct dose.